Asbabun Nuzul Sebagai Kunci Menyambungkan Wahyu Dengan Realita Sosial - Nur Annisa; Alya Nur Affifah; Neni Neni (Jurnal Budi Pekerti Agama Islam, 2025)
This article discusses the role of the asbabun nuzul (causes for revelation) or the reasons for the revelation of verses in connecting revelation with the social conditions that underlie it. This study aims to demonstrate that understanding the asbabun nuzul is crucial in interpreting the Qur'an so that the teachings of revelation can be applied appropriately and remain in line with current social realities. This study uses a literature study method by examining various classical and modern commentaries that discuss the relationship between revelation and social conditions during the time of revelation. The results show that understanding the context of the asbabun nuzul not only helps understand the reasons for the revelation of verses but also plays a role in linking them to the various problems and challenges faced by Muslims today. The asbabun nuzul plays a key role in interpreting revelation more flexibly, so that the teachings of the Qur'an can be used to respond to various social issues that arise in each time period. Overall, a strong understanding of the asbabun nuzul can broaden Muslims' insight into the Qur'an and support the application of the teachings of revelation in responding to ever-evolving social changes and dynamics.